Prof. Michael Abberton honored with NPBA lifetime achievement award - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
Prof. Michael Abberton receives the Nigeria Plant Breeders Association (NPBA) Lifetime Achievement Award, recognizing his exceptional contributions to plant breeding, agricultural research in Nigeria, and across Africa.